The Implementation of Classpoint in Learning English: A Case Study of Students at State Islamic Senior High School Medan - Nikmah Fadillah Nasution; Rahmah Fithriani; Ahmad Amin dalimunthe (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The utilization of Information and Communication technology (ICT) in educational activities substantially enhances the quality of education, particularly in the context of the current industrial revolution 4.0. Classpoint is a learning platform that helps with IT- based learning. This study seeks to evaluate the application of Classpoint in English instruction for grade XI students at State islamic high school in Medan. This Study employs a qualitative methodology utilizing a case study design. Data were gathered via observation, interviews and documentation. The data analysis methodologies encompass data reduction, data presentation, and data conclusion formulation. To guarantee the data’s validity, triangulation of data, methodologies, and source was employed. This study’s findings indicate that classpoint is highly effective in facilitating English learning for eleventh- grade students at State islamic high school in Medan.